Bronchoalveolar lavage in pulmonary mycotoxicosis (organic dust toxic syndrome). - Lecours, R (1986)
Two cases of pulmonary mycotoxicosis (organic dust toxic syndrome) are described in which bronchoalveolar lavage was undertaken during the acute phase and after recovery. Both cases occurred after exposure to mould dust in a silo in the course of removing the top mouldy layer of silage or oats at the start of unloading. The workers suffered an acute febrile illness accompanied by cough and dyspnoea. One patient had impaired ventilatory function and both had arterial desaturation in the acute phase. There was mild impairment of diffusing capacity (transfer factor). Bronchoscopy showed inflammation of the bronchial mucosa in one patient. Fungal spores were cultured from the lavage fluid in both patients. In both patients there was an increase in the percentage of neutrophils in the lavage fluid without increase in lymphocytes. The immunoglobulin concentration in the lavage fluid was normal. At the follow up lavage the neutrophils had returned to normal while a mild lymphocytosis of the lavage fluid was seen in both patients.